(untitled) (Mugda Medical College Journal, 2025)
The Danis-Weber classification system categorizes ankle fractures based on the location and appearance of the fibular fracture, with type-C fractures commonly treated with open reduction, particularly in younger individuals. However, there is limited research on outcomes for patients over 60 with these fractures. This study aimed to evaluate the radiological and functional outcomes of open reduction and internal fixation (ORIF) in patients over 60 with Danis-Weber type-C closed ankle fractures, which was conducted at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR) in Dhaka, Bangladesh, between May 2017 and August 2019. The study included 32 patients who underwent ORIF using a small dynamic compression plate (DCP) for fibular fractures and a 4mm cancellous screw for medial malleolus fractures. The average follow-up period was 24 weeks, and outcomes were assessed using the American Orthopaedic Foot and Ankle Society (AOFAS) score. Results showed that 84% of patients achieved satisfactory outcomes, with 15 classified as excellent and 12 as good. Radiological healing occurred in an average of 13.34 weeks, with no reports of talar shift, deep infection, non-union, or implant failure. Superficial infections were observed in 6% of patients, and significant correlations were found between dorsiflexion, plantarflexion, and pain scores at 12- and 24-week follow-ups. Overall, ORIF using a small DCP proved to be a safe and effective treatment for Danis-Weber type-C closed ankle fractures in older patients, with favorable outcomes, minimal complications, and short treatment durations. Mugda Med Coll J. 2024; 7(2): 66-71